Seeing is believing: methods to monitor vertebrate autophagy in vivo. Issue 10 (24th October 2018) - Lopez, Ana; Fleming, Angeleen; Rubinsztein, David C.
Abstract : Abstract : Autophagy is an intracellular clearance pathway that delivers cytoplasmic contents to the lysosome for degradation. It plays a critical role in maintaining protein homeostasis and providing nutrients under conditions where the cell is starved. It also helps to remove damaged organelles and misfolded or aggregated proteins. Thus, it is not surprising that defects in this pathway are associated with a variety of pathological conditions, such as neurodegeneration, cancer and infection. Pharmacological upregulation of autophagy is considered a promising therapeutic strategy for the treatment of neurodegenerative and infectious diseases. Studies in knockout mice have demonstrated that autophagy is essential for nervous system function, and data from invertebrate and vertebrate models suggest that the efficiency of autophagic processes generally declines with age. However, much of our understanding of the intracellular regulation of autophagy comes from in vitro studies, and there is a paucity of knowledge about how this process is regulated within different tissues and during the processes of ageing and disease. Here, we review the available tools to probe these questions in vivo within vertebrate model systems. We discuss how these tools have been used to date and consider future avenues of research.